MH370 HEADLINES: A COMPARATIVE ANALYSIS OF EMOTIVE LANGUAGE IN TWO NEWSPAPERS - ISMAIL, ISMA NOORNISA; Ahmar, Amirah Izzati Syahrul (Universitas Muhammadiyah Lampung, 2025)
The strategic use of emotive language in journalistic headlines serves to capture reader attention and evoke emotional responses. This study examines the application of emotive language in headlines related to Malaysian Airlines Flight 370 (MH370) through a comparative analysis of New Straits Times and The Washington Post. Using Martin and White's (2005) appraisal theory, the research investigates attitude systems (affect, judgement, and appreciation) and graduation systems (sharp and soft tones) in headline construction. The study adopts a qualitative approach, analyzing 10 headlines from each publication through content analysis, with headlines selected via homogeneous purposive sampling. The findings reveal that cultural context significantly influences the deployment of emotive language, with news outlets strategically leveraging social contexts to elicit specific emotional responses from their target audiences. This relationship between cultural background and emotional interpretation underscores both the power and potential risks of emotive language in headline construction. While effective use of emotive language can enhance reader engagement, its misuse may lead to sensationalism and misinterpretation of news content. These insights provide valuable guidance for researchers, journalists, and academicians in crafting effective and ethically sound headlines.